„Upaństwowienie romantyzmu” w kinie II RP. O Panu Tadeuszu w reżyserii Ryszarda Ordyńskiego - Szyngiel , Elżbieta (Załącznik Kulturoznawczy, 2018)
The article concerns the film Pan Tadeusz (1928) by Ryszard Ordyński, and issues related to the adaptation process and political reception of Mickiewicz’s artwork. In the first part of the text, the author discusses the application of 19th-century romantic ideas by the Sanacja authorities as part of their historical policy. The cult of Romanticism was realized on many levels, including everyday life as well as literature, art and journalism. Its functioning was conditioned by the existence of a holistic romantic narrative and the possibilities it brought in terms of building the continuity of tradition in social awareness. These possibilities resulted from the patriotic staffage, which over time surrounded the work of romantic bards. The second part of the text describes the tendencies dominating in Polish cinema at that time, the most important of which are the politicisation and the domination of love themes. These directions influenced the final shape of the films made in the 1920s. Afterwards, R. Ordyński’s film was presented, taking into account the political and cultural background mentioned above. The production of the picture aroused great interest among the public opinion and reviewers. The subject of discussion at that time was fidelity of the film adaptation to the literary prototype. In the article, Pan Tadeusz was presented as an example of an artwork committed to ideology. The screen trivialization of the content of Mickiewicz’s poem took place at the level of creation of a world that was simplified and devoid of romantic ambivalence, as well as in meticulous presenting details at the cost of more significant elements of the work, and intentional lowering of the level of presented content. In this way, Pan Tadeusz was a commercial undertaking, and at the same time it participated in the process of a kind of social engineering. It was a tool for building national consciousness in a reborn Polish state and, in a way, for reigning souls.